Positive plate and battery

By designing the first active material layer and the second active material layer on the positive electrode sheet of the battery, ensuring that its capacity and density ratio meets a specific ratio, the problem of lithium evolution in the middle and edge areas of the battery is solved, and the circulation performance and stability of the battery are improved .

CN119208522APending Publication Date: 2024-12-27JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411280618.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The intermediate and edge areas of existing square shell batteries are prone to lithium extraction, resulting in poor battery circulation performance. The over-hang design leads to uneven distribution of lithium ions during charging and discharging, increasing the risk of lithium extraction.

Method used

By designing the first active material layer and the second active material layer on the positive electrode sheet, it is ensured that the surface capacity of the first active material layer is greater than the second active material layer, and the surface density of the first active material layer is less than the second active material layer, thereby improving The wetting and diffusion efficiency of the electrolyte reduces edge lithium evolution.

Benefits of technology

It improves the cycling performance and stability of the battery, extends the service life of the battery, reduces the expansion of the positive electrode sheet and lithium ion accumulation, and reduces the risk of edge lithium evolution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208522A_ABST
    Figure CN119208522A_ABST
Patent Text Reader

Abstract

The invention relates to the field of batteries, and provides a positive plate and a battery. The positive plate comprises a current collector and an active material layer arranged on at least one side of the surface of the current collector, and the active material layer comprises a first active material layer and second active material layers arranged on the two sides of the first active material layer in the width direction of the current collector; the surface capacity of the first active material layer is greater than that of the second active material layer; the surface density of the first active material layer is smaller than the surface density of the second active material layer. According to the positive plate disclosed by the invention, the electrolyte can be better infiltrated, and lithium is not easy to separate out from the first active material layer and the second active material layer of the positive plate, so that the battery has better cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode sheet and a battery. Background Art

[0002] Square shell batteries, whether they are wound cells or laminated cells, are prone to poor wetting in the middle due to the long distance between the middle and the edge, and the shell is restrained at the edge, while the restraining force in the middle is relatively small, so they are prone to swelling. As the gap increases due to the expansion, the demand for electrolyte increases. However, it is difficult for the electrolyte to effectively penetrate into the middle of the cell, causing the middle of the cell to gradually deteriorate and resulting in poor battery cycle performance. The increase in the gap in the middle makes it more difficult for lithium ions to embed into the negative electrode during charging, which is prone to lithium precipitation.

[0003] And due to the existence of overhang, during the continuous charging and discharging process, the lithium content on both sides of the positive electrode sheet will accumulate. After a certain number of cycles, the CB value of the edge (referring to the capacity that the negative electrode can accept and the capacity that the positive electrode can detach) is reduced, and there is a risk of lithium precipitation. The overhang refers to the general design of the positive and negative electrode sheets, which requires the negative electrode sheet to wrap the positive electrode sheet, that is, the width of the negative electrode sheet> the width of the positive electrode sheet, and the part of the negative electrode that exceeds the width is called overhang. The reason why lithium is easily precipitated at the edge is that when charging starts, there is no lithium concentration in the overhang part. Due to the diffusion effect, the lithium in the middle will gradually diffuse to both sides. At this time, when discharging, the lithium in the overhang part will return to the edge of the positive electrode. At the same time, the edge of the positive electrode will also accept the lithium at the same position of the edge of the negative electrode. The superposition of the two causes lithium accumulation at the edge of the positive electrode.

[0004] Therefore, it is urgent to develop a positive electrode sheet that is not prone to lithium deposition in both the middle and edge regions. Summary of the invention

[0005] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a positive electrode sheet and a battery. The present invention makes the surface capacity of the first active material layer greater than the surface capacity of the second active material layer; the surface density of the first active material layer is less than the surface density of the second active material layer, so that the electrolyte has better wettability to the positive electrode sheet, and the first active material layer and the second active material layer of the positive electrode sheet are not easy to precipitate lithium, so that the battery has better cycle performance.

[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a positive electrode sheet, which includes a current collector and an active material layer arranged on at least one side of the current collector surface, the active material layer includes a first active material layer and a second active material layer respectively arranged on both sides of the first active material layer along the width direction of the current collector; the surface capacity of the first active material layer is greater than the surface capacity of the second active material layer; the surface density of the first active material layer is less than the surface density of the second active material layer.

[0007] Optionally, a ratio of the surface capacity of the first active material layer to the surface capacity of the second active material layer is less than or equal to 2.7.

[0008] Optionally, a ratio of the surface density of the first active material layer to the surface density of the second active material layer is less than or equal to 0.98.

[0009] Optionally, the surface capacity of the first active material layer is 2-4 mAh / cm 2 .

[0010] Optionally, the surface capacity of the second active material layer is 1.5-3.5 mAh / cm 2 .

[0011] Optionally, the surface density of the first active material layer is 5-40 mg / cm 2 .

[0012] Optionally, the surface density of the second active material layer is 6-45 mg / cm 2 .

[0013] Optionally, the first active material layer contains a first active material, and the second active material layer contains a second active material.

[0014] Optionally, the gram capacity of the first active substance is greater than the gram capacity of the second active substance.

[0015] Optionally, a mass content of the first active material in the first active material layer is greater than a mass content of the second active material in the second active material layer.

[0016] Optionally, the porosity of the first active material layer is greater than the porosity of the second active material layer.

[0017] Optionally, the ratio of the rolled thickness of the first active material layer to the rolled thickness of the second active material layer is 1:(0.95-1.05).

[0018] Optionally, a ratio of the gram capacity of the first active substance to the gram capacity of the second active substance is less than or equal to 1.4.

[0019] Optionally, a ratio of a mass content of the first active material in the first active material layer to a mass content of the second active material in the second active material layer is less than or equal to 1.05.

[0020] Optionally, a ratio of the porosity of the first active material layer to the porosity of the second active material layer is less than or equal to 1.07.

[0021] Optionally, the gram capacity of the first active material is 140-220 mAh / g.

[0022] Optionally, the gram capacity of the second active material is 130-210 mAh / g.

[0023] Optionally, in the first active material layer, the content of the first active material is 96-99.5 wt %.

[0024] Optionally, the porosity of the first active material layer is 20%-32%.

[0025] Optionally, the porosity of the second active material layer is 15%-30%.

[0026] Optionally, the first active material and the second active material independently include one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium manganese oxide, lithium iron manganese phosphate, and lithium iron phosphate materials.

[0027] Optionally, the first active material layer includes lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide.

[0028] Optionally, the nickel content of the first active material layer is greater than or equal to the nickel content of the second active material layer.

[0029] Optionally, the ratio of the width of the first active material layer to the width of the active material layer is (0.3-0.9):1.

[0030] A second aspect of the present invention provides a battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet is the positive electrode sheet described in the first aspect.

[0031] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0032] (1) The positive electrode sheet provided by the present invention makes the surface capacity of the first active material layer greater than the surface capacity of the second active material layer, and makes the surface density of the first active material layer less than the surface density of the second active material layer, so that the first active material layer and the second active material layer of the positive electrode sheet are not easy to precipitate lithium, which helps to improve the capacity and cycle performance of the battery.

[0033] (2) The first active material layer of the positive electrode provided by the present invention has a larger expansion space and a smaller expansion force, and the electrolyte has a stronger ability to infiltrate the positive electrode, so that the battery has better cycle performance.

[0034] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Shown is a schematic diagram of the structure of the positive electrode.

[0036] Description of Figure Numbers

[0037] 11. First active material layer; 12. Second active material layer; 13. Tab region. DETAILED DESCRIPTION

[0038] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0039] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0040] In a first aspect, the present invention provides a positive electrode sheet, the positive electrode sheet comprising a current collector and an active material layer disposed on at least one side of the current collector surface, the active material layer comprising a first active material layer and a second active material layer disposed on both sides of the first active material layer along the width direction of the current collector; the surface capacity of the first active material layer is greater than the surface capacity of the second active material layer; the surface density of the first active material layer is less than the surface density of the second active material layer. In some embodiments, Figure 1 As shown, the current collector is provided with a first active material layer 11 and a second active material layer 12 respectively provided on both sides of the first active material layer 11 along the width direction of the current collector, and the current collector is also provided with an empty foil area 13, which is provided on both sides of the second active material layer 12 away from the first active material layer 11 along the width direction of the current collector. The empty foil area is provided with a pole ear.

[0041] In some embodiments, the thickness of the first active layer is the same as or different from the thickness of the second active layer.

[0042] The surface capacity of the first active material layer is greater than that of the second active material layer, which is beneficial to promoting electrochemical reactions in the central region, improving the diffusion efficiency of lithium ions in the central region, and is beneficial to the infiltration of the first active material layer into the electrolyte, and neutralizing the problem of poor infiltration caused by the swelling of the first active material layer of the battery in the late cycle. The large surface capacity of the first active material layer is helpful to promote a more active electrochemical reaction in the first active material layer, that is, to enhance the reaction activity of the first active material layer. This enhanced activity helps to better utilize the electrolyte and ultimately improve the cycle performance of the battery. The surface capacity of the second active material layer is smaller, which is beneficial to reduce the ion diffusion rate at the edge and reduce lithium precipitation at the edge. The test method of the surface capacity is: the assembled battery is subjected to charge and discharge cycle test, the corresponding current, voltage and discharge capacity are recorded, and then the area coated with the active material is calculated = the width of the coating * the length of the coating, and finally the surface capacity is calculated = capacity / area.

[0043] The surface density of the first active material layer is smaller than that of the second active material layer, which enhances the reaction activity of the battery, reduces the expansion of the pole piece of the first active material layer, slows down the swelling of the first active material layer of the battery cell, makes the electrolyte better infiltrated, reduces the lithium precipitation of the second active material layer, and improves the overall performance and cycle stability of the battery. The smaller surface density of the first active material layer is beneficial to improving the porosity of the first active material layer, helps to improve the wettability of the electrolyte and the diffusion capacity of the active material, and can also provide more space for the expansion of the first active material layer material, thereby reducing internal stress, extending the service life of the battery, and helping to neutralize the rapid response brought by the larger surface capacity. The larger surface density of the second active material layer makes the porosity of the second active material layer lower, which is beneficial to reduce the accumulation and agglomeration of the active material, and is also beneficial to reduce the accumulation of lithium ions in the second active material layer and reduce lithium precipitation at the edge. The test method of the surface density is: punch out a small pole piece sample, and the punched area S is usually fixed to 1540.25mm 2 , the electronic balance weighs the weight m; punch out a small piece of foil of the same area, the electronic balance weighs the weight m 2 ; Calculate the surface density = (mm 2 ) / S, unit is mg / cm 2 .

[0044] When the surface capacity of the first active material layer is greater than the surface capacity of the second active material layer and the surface density of the first active material layer is less than the surface density of the second active material layer, it is beneficial to promote the electrochemical reaction of the first active material layer, enhance the reaction activity of the battery, improve the diffusion efficiency of lithium ions in the first active material layer and the wetting ability of the electrolyte to the first active material layer, neutralize the problem of poor wetting caused by the swelling of the first active material layer of the battery in the late cycle, reduce the expansion of the pole piece of the first active material layer, reduce the lithium chromatography of the second active material layer, and improve the overall performance and cycle stability of the battery. The small surface density of the first active material layer causes the first active material layer to be difficult to expand, which helps to improve the wetting performance, and is also beneficial to improve the porosity of the first active material layer and improve the wetting performance. The large surface capacity helps to improve the diffusion efficiency and promote wetting. The combination of the two helps to improve the wettability of the electrolyte to the first active material layer and the cycle performance of the battery. The surface capacity of the second active material layer is small and the surface density is large. At this time, the surface capacity is small, the diffusion rate of the electrolyte slows down, which helps to reduce lithium precipitation. The large surface density helps to reduce accumulation, which further helps to reduce lithium precipitation.

[0045] In some embodiments, the ratio of the surface capacity of the first active material layer to the surface capacity of the second active material layer is less than or equal to 2.7. When the ratio of the surface capacity of the first active material layer to the surface capacity of the second active material layer is less than or equal to 2.7, it is beneficial to promote the electrochemical reaction in the central region, improve the diffusion efficiency of lithium ions in the central region, and improve the wettability of the electrolyte to the electrode sheet, and also help to inhibit the lithium chromatography between the first active material layer and the second active material layer.

[0046] In some embodiments, the ratio of the surface density of the first active material layer to the surface density of the second active material layer is less than or equal to 0.98. When the ratio of the surface density of the first active material layer to the surface density of the second active material layer is less than or equal to 0.98, it is beneficial to reduce the expansion of the pole piece of the first active material layer, slow down the swelling of the first active material layer of the battery cell, make the electrolyte better infiltrated, and reduce the second active material layer lithium.

[0047] In some embodiments, the surface capacity of the first active material layer is 2-4 mAh / cm 2 , for example, 2 mAh / cm 2 、2.5mAh / cm 2 、3mAh / cm 2 、3.5mAh / cm 2 and 4mAh / cm 2 The surface capacity of the first active material layer is 2-4 mAh / cm 2It helps to promote a more active electrochemical reaction in the first active material layer, that is, it enhances the reaction activity of the first active material layer. This enhanced activity helps to better utilize the electrolyte and ultimately improve the cycle performance of the battery. The surface capacity is less than 2mAh / cm 2 When the electrolyte has poor wettability, the reaction activity of the first active material layer is poor, and the battery cycle performance is poor; the surface capacity is greater than 4 mAh / cm 2 When the activity is too high, the consumption of lithium ions is accelerated and the cycle stability of the battery is reduced.

[0048] In some embodiments, the surface capacity of the second active material layer is 1.5-3.5 mAh / cm 2 , for example, it can be 1.5 mAh / cm 2 、2.5mAh / cm 2 、3mAh / cm 2 、3.5mAh / cm 2 The surface capacity of the second active material layer is 1.5-3.5 mAh / cm 2 When the surface capacity is less than 1.5 mAh / cm, it is beneficial to reduce the ion diffusion rate at the edge and reduce the lithium deposition at the edge. 2 When the electrolyte has poor wettability, the battery cycle performance is poor; the surface capacity is greater than 3.5 mAh / cm 2 When the activity is too high, the consumption of lithium ions is accelerated and the cycle stability of the battery is reduced.

[0049] In some embodiments, the surface density of the first active material layer is 5-40 mg / cm 2 , for example, 5 mg / cm 2 、10mg / cm 2 、15mg / cm 2 , 20mg / cm 2 , 25mg / cm 2 、30mg / cm 2 、35mg / cm 2 and 40mg / cm 2 The surface density of the first active material layer is 5-40 mg / cm 2 It is helpful to improve the porosity of the first active material layer, which helps to improve the wettability of the electrolyte and the diffusion capacity of the active material. It can also provide more space for the expansion of the first active material layer material, thereby reducing internal stress and extending the service life of the battery. It also helps to neutralize the rapid response brought by the large surface capacity. The surface density of the first active material layer is less than 5mg / cm 2 , the pore content is too much, the energy density is low; the surface density of the first active material layer is greater than 40 mg / cm 2 , the more difficult it is for lithium ions to be embedded and removed, affecting the cycle performance.

[0050] In some embodiments, the surface density of the second active material layer is 6-45 mg / cm 2 , for example, 6 mg / cm 2 、10mg / cm 2 、15mg / cm 2 , 20mg / cm 2 , 25mg / cm 2 、30mg / cm 2 、35mg / cm 2 , 40mg / cm 2 and 45mg / cm 2 The surface density of the second active material layer is 6-45 mg / cm 2 It is beneficial to reduce the accumulation and agglomeration of active materials, and also to reduce the accumulation of lithium ions in the second active material layer and reduce edge lithium precipitation. The surface density of the second active material layer is less than 6 mg / cm 2 , it is not easy to coat on the surface of the pole piece, and the energy density is low; the surface density of the second active material layer is greater than 45 mg / cm 2 , the more difficult it is for lithium ions to be embedded and removed, affecting the cycle performance.

[0051] In some embodiments, the first active material layer includes a first active material, and the second active material layer includes a second active material.

[0052] In some embodiments, the mass content of the first active substance in the first active substance layer is greater than the mass content of the second active substance in the second active substance layer. When the mass content of the first active substance in the first active substance layer is greater than the mass content of the second active substance in the second active substance layer, it is beneficial to increase the surface capacity of the first active substance layer.

[0053] In some embodiments, the ratio of the mass content of the first active substance in the first active substance layer to the mass content of the second active substance in the second active substance layer is less than or equal to 1.05, for example, it can be 1.05, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2 and 0.1. When the ratio of the mass content of the first active substance in the first active substance layer to the mass content of the second active substance in the second active substance layer is less than or equal to 1.05, it is beneficial to improve the surface capacity of the battery, make the pole piece less likely to fall powder, and improve the cycle performance of the battery.

[0054] In some embodiments, in the first active material layer, the mass content of the first active material is 96-99.5wt%, for example, 96wt%, 97wt%, 98wt% and 99.5wt%. When the mass content of the first active material is greater than 99.5wt%, the surface capacity is high, the content of the binder in the positive electrode sheet is low, the positive electrode sheet is easy to lose powder, and the cycle performance of the battery is poor. When the content of active material in the positive electrode sheet is low, the surface capacity is reduced, the content of the binder in the positive electrode sheet is relatively high, and the excessively high content of the binder affects the activation performance, and the cycle performance will deteriorate.

[0055] In some embodiments, in the second active material layer, the mass content of the second active material is 95-98.8 wt %, for example, 95 wt %, 96 wt %, 97 wt %, 98 wt % and 98.8 wt %.

[0056] In some embodiments, the gram capacity of the first active material is greater than the gram capacity of the second active material. The test method of the gram capacity is as follows: (1) Sample preparation: First, a positive electrode sample needs to be prepared, which includes coating the active material on the current collector and undergoing pretreatment steps such as drying and compaction. (2) Assembling button cells or full batteries: Assemble the prepared positive electrode sheet with other battery components (such as counter electrode, electrolyte, and separator) into a test battery. As needed, you can choose to assemble it into a button cell or a full battery. (3) Charge and discharge test Use a battery testing system to perform charge and discharge cycle tests on the assembled battery and record the corresponding current, voltage, and capacity. (4) Calculate gram capacity = discharge capacity of the battery (mAh) divided by the mass (g) of the active material used to make this battery. The gram capacity of the first active material being greater than the gram capacity of the second active material is beneficial to promoting the electrochemical reaction in the central area, improving the diffusion efficiency of lithium ions in the central area, and improving the wettability of the electrolyte to the electrode sheet, and also helps to inhibit the lithium chromatography between the first active material layer and the second active material layer.

[0057] In some embodiments, the ratio of the gram capacity of the first active substance to the gram capacity of the second active substance is less than or equal to 1.4, for example, it can be 1.4, 1.3, 1.2, 1.1, 1, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2 and 0.1.

[0058] In some embodiments, the gram capacity of the first active material is 140-220 mAh / g, for example, 140 mAh / g, 160 mAh / g, 180 mAh / g, 200 mAh / g and 220 mAh / g. When the gram capacity of the first active material is 140-220 mAh / g, the wettability of the first active material layer of the positive electrode sheet is good, which is conducive to improving the cycle performance of the battery.

[0059] In some embodiments, the gram capacity of the second active material is 130-210 mAh / g, for example, 130 mAh / g, 150 mAh / g, 170 mAh / g, 190 mAh / g and 210 mAh / g.

[0060] In some embodiments, the first active material may include polycrystalline particles with a high proportion.

[0061] In some embodiments, when the first active material contains nickel, the first active material is an active material with a high nickel content, and the second active material is an active material with a low nickel content or other active materials with a low gram capacity. The high nickel content means that the proportion of nickel in the active material is relatively high, and the low nickel content means that the proportion of nickel in the active material is relatively low.

[0062] In some embodiments, when the first active material contains nickel, the first active material is an active material with a high nickel content and an active material with a low nickel content, and the second active material is an active material with a low nickel content or other active materials with a low gram capacity.

[0063] In some embodiments, the porosity of the first active material layer is greater than the porosity of the second active material layer. The porosity test method is a gas adsorption method: the sample is placed in a vacuum environment, and an inert gas (such as nitrogen) of known volume and pressure is gradually introduced. The gas molecules will gradually fill the pores of the material, and the pore volume can be calculated by monitoring the amount of gas adsorbed at different pressures. The porosity is calculated by combining the total mass and volume information of the sample. This method usually requires specialized instruments such as a BET analyzer to complete. Porosity is related to compaction density. When the compaction density is large, the porosity is small, and when the compaction density is small, the porosity is large.

[0064] In some embodiments, the ratio of the porosity of the first active material layer to the porosity of the second active material layer is less than or equal to 1.07, for example, it can be 1.4, 1.3, 1.2, 1.1, 1, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2 and 0.1. If the porosity of the first active material layer and the porosity of the second active material layer are too small, it is not conducive to the infiltration of the electrolyte and the release of the rebound stress of the pole piece, the expansion force of the pole piece increases, and the cycle performance of the battery is poor. When the porosity of the first active material layer and the second active material layer is too large, the expansion force of the pole piece decreases, the pole piece is easy to fall off, and the cycle performance of the battery is also slightly poor. When the ratio of the porosity of the first active material layer to the porosity of the second active material layer is less than or equal to 1.07, it is conducive to promoting the electrochemical reaction in the central area, improving the diffusion efficiency of lithium ions in the central area, and improving the wettability of the electrolyte to the pole piece, and it is also helpful to inhibit the first active material layer and the second active material layer from stratifying lithium. When the ratio of the porosity of the first active material layer to the porosity of the second active material layer is greater than 1.07, lithium deposition is likely to occur in the second active material layer, and the first active material layer of the battery cell is likely to swell, resulting in poor battery cycle performance. Therefore, when the ratio of the porosity of the first active material layer to the second active material layer is within the scope of the present invention, the electrolyte has good wettability on the pole piece, the pole piece is not likely to shed powder, and the battery cycle performance is good.

[0065] In some embodiments, the porosity of the first active material layer is 20%-32%, such as 20%, 22%, 24%, 26%, 28%, 30% and 32%. When the porosity of the first active material layer is less than 20%, the expansion force of the battery is greater and the battery cycle performance is poor. When the porosity of the first active material layer is greater than 32%, it means that the compaction density of the battery needs to be very large and close to the critical value. When the compaction density is too large, the pole piece is prone to powdering, which is not conducive to improving the wetting ability of the electrolyte of the first active material layer to the pole piece, and the battery cycle performance deteriorates.

[0066] In some embodiments, the porosity of the second active material layer is 15%-30%, such as 15%, 17%, 19%, 21%, 23%, 25%, 27% and 30%. When the porosity of the second active material layer is less than 15%, the wettability of the electrolyte to the electrode is poor, resulting in poor cycle performance of the battery. When the porosity of the second active material layer is greater than 30%, it means that the compaction density of the battery needs to be very large, close to the critical value. When the compaction density is too large, the electrode is prone to powdering, which is not conducive to improving the wettability of the electrolyte of the first active material layer to the electrode, and the cycle performance of the battery deteriorates.

[0067] In some embodiments, the ratio of the rolled thickness of the first active material layer to the rolled thickness of the second active layer material is 1:(0.95-1.05). Under the same coating density, the smaller the rolled thickness of the second active material layer, the greater the compaction density and the smaller the porosity. The small pores of the second active material layer will lead to poor wetting on both sides, affecting the cycle performance. The rolled thickness of the second active material layer is larger, the larger the porosity, the smaller the expansion force, and the easier it is to lose powder, which is not conducive to the wetting of the first active material layer area and the cycle deterioration. Therefore, when the rolled thickness of the first active material layer and the rolled thickness of the second active material layer are within the protection scope of the present invention, the cycle performance of the battery is better. Preferably, in order to process and ensure battery performance, the rolled thickness of the first active material layer is equal to the rolled thickness of the second active layer material.

[0068] In some embodiments, the first active material and the second active material each independently include one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium manganese oxide, lithium iron manganese phosphate, and lithium iron phosphate materials.

[0069] In some embodiments, the first active material layer includes lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide.

[0070] In some embodiments, the nickel content of the first active material layer is greater than or equal to the nickel content of the second active material layer.

[0071] In some embodiments, the ratio of the width of the first active material layer to the width of the active material layer is (0.3-0.9):1, for example, it can be 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1 and 0.9:1. When the ratio of the width of the first active material layer to the width of the active material layer is less than 0.3, the area of ​​the first active material layer is small, the wettability of the battery is poor, the cycle performance of the battery is also poor, and the porosity of the first active material layer is larger than that of the second active material layer. At this time, the area of ​​the first active material layer accounts for a small proportion, but the porosity is large, the expansion force is easy to become large, and the cycle performance of the battery is poor; when the ratio of the width of the first active material layer to the width of the active material layer is greater than 0.9, the area of ​​the first active material layer is large, and the area with faster reaction active area is larger, which accelerates the consumption rate of lithium ions, reduces the cycle stability of the battery, and the cycle performance of the battery is poor.

[0072] In some embodiments, the method for preparing the positive electrode sheet includes:

[0073] preparing a first active material slurry;

[0074] preparing a second active material slurry;

[0075] The first active material slurry is applied to the middle region of the current collector to form a first active material layer, and the second active material slurry is applied to both sides of the middle region along the width direction of the current collector to form a second active material layer.

[0076] In some embodiments, the first active material slurry includes a first active material, a conductive agent, and a binder.

[0077] In some embodiments, the choice of the binder is not specifically limited as long as it can meet actual needs. For example, the binder can be selected from at least one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride, polyacrylic acid, sodium polyacrylate, polyacrylamide, sodium alginate, polyvinyl alcohol, sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene and polyethylene oxide.

[0078] In some embodiments, the selection of the conductive agent is not particularly limited as long as it can meet actual needs, such as at least one of carbon black, conductive graphite, carbon fiber, carbon nanotube (CNT) and graphene.

[0079] In some embodiments, in the first active material slurry, the content of the first active material is 96-99%, the content of the conductive agent is 0-2%, and the content of the binder is 1-3.5%.

[0080] In some embodiments, the second active material slurry includes a second active material, a conductive agent, and a binder.

[0081] In some embodiments, in the second active material slurry, the content of the second active material is 95-98.8%, the content of the conductive agent is 0-2%, and the content of the binder is 1.2-3.5%.

[0082] For specific components of the first active material slurry and the second active material slurry, please refer to the first active material layer and the second active material layer.

[0083] A second aspect of the present invention provides a battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet is the positive electrode sheet described in the first aspect.

[0084] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0085] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0086] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0087] Example 1

[0088] This example is used to illustrate the preparation of the positive electrode sheet of the present invention.

[0089] Preparation of positive electrode slurry:

[0090] The first active material slurry 400g: lithium nickel cobalt manganese oxide (single crystal, gram capacity 185mAh / g) 392g, conductive agent carbon black 2g, polyvinylidene fluoride 6g.

[0091] The second active material slurry 171g: lithium nickel cobalt manganese oxide (single crystal, gram capacity 180mAh / g) 164g, conductive agent carbon black 2.6g, polyvinylidene fluoride 4.3g.

[0092] The first active material slurry is applied to the first active material layer of the current collector along the width direction of the current collector, with a coating surface density of 14.28 mg / cm 2 , rolling thickness 0.08mm, coating width 70mm, to obtain the first active material layer; the second active material slurry was coated on both sides of the first active material layer on the current collector along the width direction of the current collector, with a coating surface density of 14.61mg / cm 2 The rolling thickness is 0.08mm and the coating width is 30mm to obtain the positive electrode sheet.

[0093] Preparation of negative electrode slurry:

[0094] 350 g of negative electrode slurry: 336 g of artificial graphite, 5.25 g of styrene-butadiene rubber, 3.5 g of sodium carboxymethyl cellulose, and 5.25 g of carbon black. The negative electrode slurry is coated on a negative electrode current collector to obtain a negative electrode sheet.

[0095] Electrolyte 250g: Lithium hexafluorophosphate (LiPF 6 ) is dissolved in a mixed solvent consisting of ethylene carbonate (EC), dimethyl carbonate (DEC) and ethyl methyl carbonate (EMC) (the mass ratio of the three is 1:1:1) to obtain an electrolyte.

[0096] Diaphragm: A 7 μm thick PE diaphragm (polyethylene) was used, with a 3 μm ceramic layer and a 3 μm polyvinylidene fluoride (PVDF) layer coated on both sides.

[0097] Battery assembly: Assemble the positive electrode sheet, negative electrode sheet and separator to obtain a battery cell, and inject electrolyte into it to obtain a battery.

[0098] In Example 2 to Example 9, and Comparative Examples 1-3, the method of Example 1 was followed, and the specific different characteristics are shown in Table 1.

[0099] The Example 2 group was operated according to the method of Example 1, except that the surface capacity of the first active material layer was different from the surface capacity of the second active material layer.

[0100] Example 2-1 is operated according to the method of Example 1, except that the ternary single crystal material of the first active material layer is changed into a single crystal + polycrystalline combination material.

[0101] Example 2-2 is operated according to the method of Example 1, except that the ternary single crystal material of the first active material layer is changed into a mixed material of single crystal and polycrystalline.

[0102] The Example 3 group was operated according to the method of the Example 1, except that the surface density of the first active material layer was different from the surface density of the second active material layer.

[0103] The fourth embodiment group was operated according to the method of the first embodiment, except that the porosity of the first active material layer was different from the porosity of the second active material layer.

[0104] The fifth embodiment group was operated according to the method of the first embodiment, except that the width of the first active material layer was different from the width of the second active material layer.

[0105] The Example 6 group was operated according to the method of Example 1, except that the contents of the first active substance and the second active substance were different.

[0106] The Example 7 group was operated according to the method of the Example 1, except that the rolling thickness of the first active material layer and the second active material layer was different.

[0107] The eighth embodiment group was operated according to the method of the first embodiment, except that the first active layer and the second active layer were changed to lithium iron phosphate material.

[0108] Comparative Example 1 was operated according to the method of Example 1, except that the surface capacity of the first active material layer was smaller than the surface capacity of the second active material layer.

[0109] Comparative Example 2 is operated according to the method of Example 1, except that the surface density of the first active material layer is greater than the surface density of the second active material layer.

[0110] Comparative Example 3 is operated according to the method of Example 1, except that the surface capacity of the first active material layer is smaller than the surface capacity of the second active material layer, and the surface density of the first active material layer is greater than the surface density of the second active material layer.

[0111] Table 1

[0112]

[0113] Table 2

[0114]

[0115] Test method:

[0116] The embodiments and comparative examples were tested according to the following test methods, and the specific results are shown in Table 3.

[0117] (1) 25℃ cycle test: The battery is placed in an environment of 25℃ and charged at a current rate of 1C to the charge cut-off voltage, then left to stand for 30 min. It is then discharged at a current rate of 1C to the discharge cut-off voltage and left to stand for 30 min. This process is one cycle. Repeat this process and record the discharge capacity Cn of each cycle, the first discharge capacity C0, the capacity retention rate of the nth cycle Cn / C0, and the number of cycles at which the capacity retention rate reaches 80%.

[0118] (2) Expansion force test: When performing test 1, a clamp equipped with a pressure sensor is used. The initial preload force of the clamp is 300 kgf. At the end of the cycle, when the cycle reaches 80% SOH, the discharge expansion force is recorded.

[0119] (3) Lithium deposition test: The battery is cycled 20 times according to the steps of test 1 and then fully charged to 100% SOC. The battery is disassembled to check the degree of lithium deposition.

[0120] The relevant test results and analysis can be seen in Table 3.

[0121] Table 3

[0122]

[0123] In Example 2-1, the ternary single crystal material of the first active material zone is changed into a material combining single crystal and polycrystalline. The electrolyte in the middle area of ​​the battery has good wettability to the electrode, which is beneficial to improving the cycle performance of the battery.

[0124] The surface capacity of the first active material layer of the positive electrode sheet of Comparative Example 1 is smaller than the surface capacity of the second active material layer, and lithium deposition is easily generated in the first active material layer, resulting in poor cycle performance.

[0125] The surface density of the first active material layer of the positive electrode sheet of Comparative Example 2 is greater than the surface density of the second active material layer. The electrode sheet with the second active material layer is not easily wetted by the electrolyte and is prone to lithium deposition. In addition, the rebound ability of the first active material layer deteriorates, the expansion force increases, and the cycle performance deteriorates.

[0126] The activity of the first active material layer of the positive electrode sheet of Comparative Example 3 deteriorated, the lithium chromatography between the first active material layer and the second active material layer was serious, and the cycle performance was even worse.

[0127] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0128] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode sheet includes a current collector and an active material layer arranged on at least one side of the current collector surface, the active material layer includes a first active material layer and a second active material layer respectively arranged on both sides of the first active material layer along the width direction of the current collector; the surface capacity of the first active material layer is greater than the surface capacity of the second active material layer; the surface density of the first active material layer is less than the surface density of the second active material layer.

2. The positive electrode sheet according to claim 1, characterized in that: The ratio of the surface capacity of the first active material layer to the surface capacity of the second active material layer is less than or equal to 2.7; and / or, The ratio of the surface density of the first active material layer to the surface density of the second active material layer is less than or equal to 0.

98.

3. The positive electrode sheet according to claim 1 or 2, characterized in that: The surface capacity of the first active material layer is 2-4 mAh / cm 2 and / or, The surface capacity of the second active material layer is 1.5-3.5 mAh / cm 2 and / or, The surface density of the first active material layer is 5-40 mg / cm 2 and / or, The surface density of the second active material layer is 6-45 mg / cm 2 .

4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The first active material layer includes a first active material, and the second active material layer includes a second active material. Preferably, the gram capacity of the first active substance is greater than the gram capacity of the second active substance; Preferably, the mass content of the first active substance in the first active substance layer is greater than the mass content of the second active substance in the second active substance layer; and / or, The porosity of the first active material layer is greater than the porosity of the second active material layer; and / or, The ratio of the rolled thickness of the first active material layer to the rolled thickness of the second active material layer is 1:(0.95-1.05).

5. The positive electrode sheet according to claim 4, characterized in that: The ratio of the gram capacity of the first active substance to the gram capacity of the second active substance is less than or equal to 1.4; and / or, The ratio of the mass content of the first active material in the first active material layer to the mass content of the second active material in the second active material layer is less than or equal to 1.05; and / or, A ratio of the porosity of the first active material layer to the porosity of the second active material layer is less than or equal to 1.

07.

6. The positive electrode sheet according to claim 4 or 5, characterized in that: The gram capacity of the first active substance is 140-220 mAh / g; and / or, The gram capacity of the second active substance is 130-210 mAh / g; and / or, In the first active material layer, the mass content of the first active material is 96-99.5wt%; and / or, In the second active material layer, the mass content of the second active material is 95-98.8wt%; and / or, The porosity of the first active material layer is 20%-32%; and / or, The porosity of the second active material layer is 15%-30%.

7. The positive electrode sheet according to any one of claims 4 to 6, characterized in that: The first active material and the second active material each independently include one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium manganese oxide, lithium iron manganese phosphate, and lithium iron phosphate materials; Preferably, the first active material layer includes lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide.

8. The positive electrode sheet according to any one of claims 4 to 7, characterized in that: The nickel content of the first active material layer is greater than or equal to the nickel content of the second active material layer.

9. The positive electrode sheet according to any one of claims 1 to 8, characterized in that: The ratio of the width of the first active material layer to the width of the active material layer is (0.3-0.9):

1.

10. A battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet and a separator, and the positive electrode sheet is the positive electrode sheet according to any one of claims 1 to 9.